Case Management of Respiratory Failure in Pneumonia: Literature Review - Dinda Nur Rohmah (Jurnal Berita Ilmu Keperawatan, 2020)
Introduction: Respiratory failure is a frequent condition in critically ill patients that is associated with a high mortality rate, especially when invasive mechanical ventilation is required. In many case fever, cough, sputum and shortness of breath occur. Severe respiratory failure can lead to severe respiratory infections, such as lung infections (pneumonia). Methoda: a literature review research method in the form of a case report through searches for accredited journal sites such as Sciendirect and Elsevier with the keywords respiratory failure in pneumonia in the 2015-2020 period. Research result: in handling pneumonia cases, each country has its own way, consisting of physical examination, blood laboratory test, chest x-rays, chest CT scan, sputum culture examination, pxygen installation, mechanical ventilation and administration of drugs such as piperacillin-tazobactim, levlofoxacin, ceftriaxone, oseltamivir, azithromycin, each patient is deffernt based on the history of pain suffered. Conclusion: each region and every country has its own way of dealing with pneumonia until now the disease is the most common cause of in out patient hospital clinics in various countries.